A new head-mounted display-based augmented reality system in neurosurgical oncology: a study on phantom. Issue 1 (1st January 2017) - Cutolo, Fabrizio; Meola, Antonio; Carbone, Marina; Sinceri, Sara; Cagnazzo, Federico; Denaro, Ennio; Esposito, Nicola; Ferrari, Mauro; Ferrari, Vincenzo
Abstract: Purpose: Benefits of minimally invasive neurosurgery mandate the development of ergonomic paradigms for neuronavigation. Augmented Reality (AR) systems can overcome the shortcomings of commercial neuronavigators. The aim of this work is to apply a novel AR system, based on a head-mounted stereoscopic video see-through display, as an aid in complex neurological lesion targeting. Effectiveness was investigated on a newly designed patient-specific head mannequin featuring an anatomically realistic brain phantom with embedded synthetically created tumors and eloquent areas. Materials and methods: A two-phase evaluation process was adopted in a simulated small tumor resection adjacent to Broca's area. Phase I involved nine subjects without neurosurgical training in performing spatial judgment tasks. In Phase II, three surgeons were involved in assessing the effectiveness of the AR-neuronavigator in performing brain tumor targeting on a patient-specific head phantom. Results: Phase I revealed the ability of the AR scene to evoke depth perception under different visualization modalities. Phase II confirmed the potentialities of the AR-neuronavigator in aiding the determination of the optimal surgical access to the surgical target. Conclusions: The AR-neuronavigator is intuitive, easy-to-use, and provides three-dimensional augmented information in a perceptually-correct way. The system proved to be effective in guiding skin incision, craniotomy, and lesion targeting. The preliminary results encourage a structured study to prove clinical effectiveness. Moreover, our testing platform might be used to facilitate training in brain tumour resection procedures.